Effect of Vitamin D3 Supplementation on the Level of 25(OH)D3, Osteocalcin, and HbA1c in Children with Type 1 Diabetes Mellitus: Vitamin D3 and Type 1 DM - Hajeng Wulandari; Harjoedi Adji Tjahjono; Edi Widjajanto (Journal of Tropical Life Science, 2022)
Type 1 diabetes mellitus (T1DM) is a chronic disease caused by insulin deficiency resulting from autoimmune destruction of pancreatic beta cells. Increased risk of fractures and osteoporosis in T1DM is associated with reducing osteoblast proliferation, survival, and activity. Osteocalcin (OC) is a marker of late-stage osteoblast differentiation. It might be positively modulated by vitamin D. This study was aimed to investigate the effect of vitamin D3 supplementation on the level of 25(OH)D3, HbA1c, and OC in children with T1DM. A randomized clinical trial was conducted to measures the levels of 25(OH)D3, HbA1c, and OC in children with T1DM supplemented with vitamin D3. Many 26 children with T1DM were equally assigned into two groups: control (standardized insulin treatment) and treatment group (standardized insulin treatment + vitamin D3 2000 IU/day). Subject characteristics showed that the subjects were predominantly female (15/26), well-nourished (19/26), the average age is 12,31 Â± 3,069 year, and the dose of insulin average is 1,17 Â± 0,233 IU/kg BW/day. Our data demonstrated that vitamin D3 treatment significantly increased the level of 25(OH)D3 and improved glycemic control, represented by a low HbA1c level. However, there was no significant difference in OC level in both groups (independent t-test, p > 0.05). Further analysis showed no significant relationship between the level of 25(OH)D3, HbA1c, and OC. We concluded that vitamin D3 supplementation improves children's glycemic control with T1DM, but no significant alteration on OC levels.Keywords: HbA1c, Osteocalcin, T1DM, Vitamin D